(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Currently, attractive systematic civic is eco-friendly with an emerging way of synthesizing nanoparticles (NPs), since green synthesis is employed all over the world. Validated methods have all been used to evaluate the synthesized SiO2 NPs/JCL. When synthesizing SiO2 NPs/JCL are effectively active for the solar still process, an effect of SBSS is 82.26%. In accordance with the local climatic conditions in Vijayawada, Andhra Pradesh, India, the SBSS has produced a total distillate output of 8.79 L/day (SiO2 NPs/JCL) during the summer and 6.49 L/day (SiO2 NPs